2015
DOI: 10.1186/s13287-015-0154-6
|View full text |Cite
|
Sign up to set email alerts
|

In vivo hepatogenic capacity and therapeutic potential of stem cells from human exfoliated deciduous teeth in liver fibrosis in mice

Abstract: IntroductionLiver transplantation is a gold standard treatment for intractable liver diseases. Because of the shortage of donor organs, alternative therapies have been required. Due to their potential to differentiate into a variety of mature cells, stem cells are considered feasible cell sources for liver regeneration. Stem cells from human exfoliated deciduous teeth (SHED) exhibit hepatogenic capability in vitro. In this study, we investigated their in vivo capabilities of homing and hepatocyte differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 62 publications
3
71
0
2
Order By: Relevance
“…For purpose of treating acute renal injury induced by intramuscular injection of glycerol, SHED are revealed to incorporate into tubular, intertubular, perivascular, and glomerulus regions of kidney following intravenous or intraperitoneal injection . It was also reported that SHED are capable of differentiating into hepatocyte‐like cells directly without fusion in mouse models of carbon tetrachloride‐induced liver fibrosis, therefore recovering liver disfunction . In a recent mouse in vivo study, dental pulp pluripotent‐like stem cells (DPPSCs), a subset of DPSCs expressing pluripotency markers including OCT4, Sox2, and NANOG, are demonstrated to integrate in αSMA‐positive smooth muscle layer of blood vessels in skin wounds and dystrophic muscles, in concordance with their robust in vitro smooth muscle cell differentiation potential.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…For purpose of treating acute renal injury induced by intramuscular injection of glycerol, SHED are revealed to incorporate into tubular, intertubular, perivascular, and glomerulus regions of kidney following intravenous or intraperitoneal injection . It was also reported that SHED are capable of differentiating into hepatocyte‐like cells directly without fusion in mouse models of carbon tetrachloride‐induced liver fibrosis, therefore recovering liver disfunction . In a recent mouse in vivo study, dental pulp pluripotent‐like stem cells (DPPSCs), a subset of DPSCs expressing pluripotency markers including OCT4, Sox2, and NANOG, are demonstrated to integrate in αSMA‐positive smooth muscle layer of blood vessels in skin wounds and dystrophic muscles, in concordance with their robust in vitro smooth muscle cell differentiation potential.…”
Section: Introductionmentioning
confidence: 73%
“…107 118 Additionally, predifferentiated PSCs, including hepatocytes, 125 myocytes, 128 osteoblasts, 143 islet-like cell cluster, 45 and keratocytes, 137 Table 3, such as calvarial defect, 110 cerebral ischemia, 116,117 and limbal stem cell deficiency, 38 It was also reported that SHED are capable of differentiating into hepatocyte-like cells directly without fusion in mouse models of carbon tetrachloride-induced liver fibrosis, therefore recovering liver disfunction. 41 In a recent mouse in vivo study, 12…”
Section: Exogenous Recombinant Growth Factors a Variety Of Exogenousmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other human stem cells, SHED represent an interesting stem cell source and are obtained using non-invasive techniques. To date, SHED have been used to treat diseases such as pulp-pulp dentin regeneration (Rosa, Zhang, Grande, & Nor, 2013), jaw regeneration (Jahanbin et al, 2015), nervous system diseases (Taghipour et al, 2012), immune system diseases (Ma et al, 2012), corneal injury (Gomes et al, 2010), liver injury (Yamaza et al, 2015), lung injury (Wakayama et al, 2015), kidney injury (Hattori et al, 2015) and diabetes (Kanafi et al, 2013). However, it is unknown whether SHED have effect on the hyposalivation caused by SS.…”
mentioning
confidence: 99%
“…Exfoliated deciduous teeth are usually discarded as medical waste; therefore, SHED can be easily collected from exfoliated deciduous teeth with cooperation and agreement from the patient. SHED express embryonic stem cell markers Oct-4 and Nanog, the mesenchymal stem cell marker stromal precursor antigen-1 (STRO-1), and the neuronal stem cell marker Nestin and possess high prolifer-ation capacity; SHED also show multidifferentiation potential and can differentiate into neuronal, osteogenic, adipogenic, and hepatogenic cells (Ma et al, 2012;Miura et al, 2003;Yamaza et al, 2015). SHED have been shown to be able to differentiate into neurons, astrocytes, and oligodendrocytes (Jarmalavičiūtė et al, 2013;Miura et al, 2003;Nourbakhsh et al, 2011;Sakai et al, 2012).…”
Section: Introductionmentioning
confidence: 99%